Analisis Keamanan Website Pendaftaran Mahasiswa Baru Dengan Munggunakan Metode Vulnerability Assessment - Hafsari, Sherli Ameilia; Harjono, Harjono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The website plays an important role in the educational context, such as in managing the academic system, accepting new students, and other functions. Publications carried out online by utilizing the official campus website can make it easier for parents or student registrants from areas outside the city or even outside the island to find complete information about the desired university. Universitas Muhammadiyah Purwokerto has an online student registration system through a pmb.ump.ac.id website. An agency or organization can suffer losses if the information obtained falls to unauthorized parties, so an information system must have the ability to overcome and stop the desired bad steps. To prevent these events, this research was applied using the Vulnerability Assessment method with the aim of obtaining information on security gaps and vulnerabilities on the new student registration website of Universitas Muhammadiyah Purwokerto. The test results obtained using the vulnerability tool found a number of security holes on the new student registration website of the University of Muhammadiyah Purwokerto. Researchers have provided several recommendations to address the findings of security holes that can be used.